The effectiness of internal audit in Malaysian public sector - Ahmad, Halimah@Nasibah; Othman, Radiah; Othman, Rohana; Jusoff, Kamaruzaman (David Publishing Company, 2009)
Internal audit in Malaysian public and private sector organizations underwent a steady organic growth since gaining a foothold in the management process in the 1970s. The management of the Malaysian public sector is continuously maturing in facilitating foreign input in national development, echoing similar advances expounded by the internal audit units of private sector organizations. The main difference being the public sector addresses the interest of a much wider group of stakeholders. Rapid development in infrastructures and industries positioned Malaysia on the fringes of globalization and the world market. This enlarges the crucial role of internal auditing to ensure transparency, integrity, quality and improved service delivery; among myriad positive aims, remain the end point of any process area. This study explored the significance of internal auditing in the Malaysian public sector, and its subsequent extent and influence in public sector hierarchy and decision making. Data was collected from responses to a questionnaire distributed to head of internal auditors, internal auditors and other staff of internal audit departments from various categories of public sector departments and agencies in Malaysia. The study concluded that the internal audit function in the public sector in Malaysia is curtailed by understaffing and hampered by inadequate support from top management while, the auditors seldom extend their full cooperation. The auditors themselves lack appropriate knowledge and training on effective auditing approaches. The negative perception accorded to internal audit led to inaction by management on recommended remedies which only serve to nullify the positive contribution internal audit potentially holds to elevate the service delivery quality of the public sector.